Análise de sintomas musculoesqueléticos em atletas de padel e sua relação com o tempo de treinamentona modalidade - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The present study aimed to identify the musculoskeletal symptoms in padel athletes, and investigate whether there is an association of them with the time of practice in the modality. In this cross-sectional study, padel practitioners of both sexes, from 18 to 40 years of age, were included, in which they answered a questionnaire, including personal data and aspects of training. To evaluate musculoskeletal symptoms, the athletes answered the Nordic Questionnaire of Musculoskeletal Symptoms (NQMS) about musculoskeletal dysfunctions in the last 12 months. As a result, 54 padel practitioners were included, with an average age of 39.7±8.42 years, 63% of whom were male. It was also identified that 37% of the participants had some musculoskeletal symptom, and the places most affected by pain were the lowback region (59.3%), shoulders (50%) and knees (46.3%) respectively. Most of the athletes (87%) with longer practice time did not report symptoms of cervical pain, while in those with shorter practice time, almost half reported feeling pain in this body segment (45.7%). We conclude that the prevalence of musculoskeletal complaints is high in this sample of athletes studied, highlighting the lumbar region as the most significant. In addition, the experienced athletes had fewer cervical complaints than the beginners. Based on these results, it is suggested to create preventive strategies, considering the level of experience of the athletes.
Analysis of musculoskeletal symptoms in padel athletes and their relationship with time of the training in the modality
Keywords: Athletes; Pain; Injuries; Atletas; Dor; Lesões; Padel; CNPQ::CIENCIAS DA SAUDE